2007
DOI: 10.1080/17453670710014644
|View full text |Cite
|
Sign up to set email alerts
|

Ewing sarcoma of the rib—initial symptoms and clinical features: Tumor missed at the first visit in 21 of 26 patients

Abstract: Background and purpose Doctor's delay in diagnosing Ewing sarcoma is often long. We examined the initial symptoms of Ewing sarcoma of the rib to find characteristics that could help to shorten the delay in diagnosis and hopefully influence the prognosis.Patients and methods We examined the records from the first visit for symptoms related to Ewing sarcoma of the rib in 26 consecutive patients, all of whom were < 30 years of age and had been diagnosed between 1981 and 2000. All patients had a minimum of 5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 8 publications
0
19
0
3
Order By: Relevance
“…The importance of a radical surgery has been demonstrated by several authors (5,13,15,16): by intraoperative examination of soft tissue margin and the limit of 2 cm on the bone, in our series, we obtained a radical resection in all cases of PST; however, in case of SST we considered as acceptable a marginal resection, but always excluding an intralesional resection. As a result, all the operations were margin free, minimizing the incidence of local recurrence (8% in our series).…”
Section: A B a B Cmentioning
confidence: 90%
See 2 more Smart Citations
“…The importance of a radical surgery has been demonstrated by several authors (5,13,15,16): by intraoperative examination of soft tissue margin and the limit of 2 cm on the bone, in our series, we obtained a radical resection in all cases of PST; however, in case of SST we considered as acceptable a marginal resection, but always excluding an intralesional resection. As a result, all the operations were margin free, minimizing the incidence of local recurrence (8% in our series).…”
Section: A B a B Cmentioning
confidence: 90%
“…In the large populationbased study of Scandinavian Sarcoma Group, is clearly demonstrated the influence of wide free margins on survival; patients radically treated have higher probability of survival at 10 years (92%) compared with intralesional resections (13). Also others authors previously showed a better outcome in term of OS for patients surgically treated without margin involvement (1,19,22).…”
Section: A B a B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,7] Rate of local recurrence of chondrosarcoma has been reported as highly dependent on surgical margin, ranging from 4% to 73%. [8] In treatment of soft tissue sarcoma on lower and upper extremities, compartment resection approach has been the accepted mode of treatment, but no such approach has existed for chest wall sarcoma. Primary tumor easily infiltrates ribs and skeletal tissue, necessitating resection of chest wall.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the 10-year survival rate was 47% and the local recurrence rate 73% in patients treated with an intralesional approach. Prognostic factors for local recurrence included both surgical margins and histologic grade (17).…”
Section: Treatmentmentioning
confidence: 99%